(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2020)
This article reports on the reaction of 2-hetaryl-2-(furanyl-2-ylidene)acetonitriles with aromatic amines as N-nucleophiles. 2-Hetaryl-2-(furanyl-2-ylidene)acetonitriles represent versatile building blocks in syntheses of ω-(N-aryl)alkyl substituted heterocycles due to the presence of 1,3-bielectrophilic acrylonitrile fragment functionalized with unsaturated heterocyclic ring and nucleophilic azaheterocyclic moiety. The carbonyl group masked within the N-arylpyrrolidinylidene fragment which undergoes a ring opening through the reaction with nucleophiles. So, a method for the synthesis of 2-hetaryl-6-hydroxy-3-(arylamino)hex-2-enenitriles and 2-hetaryl-2-(N-arylpyrrolidin-2-ylidene)acetonitriles has been developed by us. The proposed scheme is based on the available reagents using. As a result of Michael addition, the aromatic amines to 2-hetaryl-2-(furanyl-2-ylidene)acetonitriles followed by ring transformations has formed two types of products, depending on the reaction conditions. The reaction of substituted furanylylideneacetonitriles with aromatic amines proceeds in good to high yields affording the corresponding 3-(arylamino)hex-2-enenitriles and 2-(N-arylpyrrolidin-2-ylidene)acetonitriles derivatives. The stereochemistry of the ring-opening reaction follows the rules of a classical SN2 mechanism. The resulting linear products can be cyclized to 2-hetaryl-2-(furanyl-2-ylidene)acetonitriles in high yields by treatment with the catalytic amount of acid or the equimolar amount of aromatic amines. Under these conditions 2-hetaryl-6-hydroxy-3-(arylamino)hex-2-enenitriles arising from reaction gives the ring closure.